Understanding the retirement-consumption puzzle through the lens of food consumption-fuzzy regression-discontinuity evidence from urban China. (December 2017) - Chen, Qihui; Deng, Tinghe; Bai, Junfei; He, Xiurong
Highlights: We analyze impacts of retirement on elderly males' food consumption in urban China. Retirement reduces elderly males' food expenditure by about 50%. Retirement barely changes elderly males' total calorie intakes. Elderly males consume less fat and protein and more carbohydrate upon retirement. Retirement has a significantly negative impact on elderly males' diet balance. Abstract: This paper provides an understanding of the widely-documented retirement-consumption puzzle from the perspective of food consumption. Exploiting the mandatory retirement age cut-off for public-sector male employees in urban China to obtain a source of exogenous variation in their retirement status, this paper identifies the causal impacts of retirement on four major aspects of their food consumption: food expenditure, time spent in food acquisition, the quantity and quality of food consumed. Based on data from the China Health and Nutrition Survey, our fuzzy regression-discontinuity analysis finds that, consistent with the retirement-consumption puzzle, retirement reduces elderly males' total food expenditure by 49–55%. However, retirement barely changes the quantity of food they consume (measured by total calorie intakes). Further analysis suggests that elderly males substitute time for money in food acquisition upon retirement, which helps to reconcile the differential impacts of retirement on food expenditure and food consumption. Finally, retirement greatly changes elderly males' diet structure. They consume significantly less food with animal origins (and thus less fat and protein) and more grains (and thus more carbohydrate) upon retirement, which undermines their diet balance by the standards provided by the Chinese Nutrition Association.